Young natives, migrants, stakeholders and health decisions at school: scoping review protocol - Catarina Afonso; Ana Spínola; Alcinda Reis; Celeste Godinho; Fátima Saragoila; Marta Rosa; Pedro Melo (Millenium, 2025)
Introduction: Low health literacy, reflected in difficulties in accessing and understanding information, limits migrants in their use of health programmes, contributing to ineffective self-management of health/disease. The literature points to the need to implement strategies that promote a more active role for young people in the health education process, enabling them to acquire skills in the areas of communication, critical thinking, and problem-solving.